Memorandum of Understanding between Comprehensive Disaster Management Porgramme (CDMP), Management Support Unit (MSU) and Brac University (2014) - Comprehensive Disaster Management Porgramme (CDMP), Management Support Unit (MSU); Brac University (Brac University and Comprehensive Disaster Management Porgramme (CDMP), Management Support Unit (MSU), 2019)
The agreement made between Comprehensive Disaster Management Porgramme (CDMP), Management Support Unit (MSU) and Brac University for implementation of improving Online Knowledge and lnformation Management System at DMIC.